2017
DOI: 10.5455/medscience.2017.06.8648
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on pathophysiology of primary dysmenorrhea under the light of alterations in complete blood count parameters

Abstract: The present study strives to evaluate how the components of complete blood count are altered in women with primary dysmenorrhea. This is a cross-sectional analysis of 155 women with primary dysmenorrhea and 155 women without dysmenorrhea. The primary dysmenorrhea and control groups were matched with respect to age and body mass index. When compared with the controls, the women with primary dysmenorrhea had a significantly younger menarche age, longer menstrual duration, higher leukocyte counts, higher neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Hal ini dapat dikarenakan asupan lemak merupakan prekursor pembentukan prostaglandin yang berperan dalam menyebabkan dysmenorrhea (Mesele et al, 2022;Huang et al, 2022;Mohammadi et al, 2022). Prostaglandin ini menyebabkan meningkatnya kontraksi miometrium dan vasokontriksi yang mengakibatkan terjadinya iskemia uterus sehingga menimbulkan rasa nyeri (Bernardi et al, 2017).…”
Section: Metodeunclassified
“…Hal ini dapat dikarenakan asupan lemak merupakan prekursor pembentukan prostaglandin yang berperan dalam menyebabkan dysmenorrhea (Mesele et al, 2022;Huang et al, 2022;Mohammadi et al, 2022). Prostaglandin ini menyebabkan meningkatnya kontraksi miometrium dan vasokontriksi yang mengakibatkan terjadinya iskemia uterus sehingga menimbulkan rasa nyeri (Bernardi et al, 2017).…”
Section: Metodeunclassified
“…It has been shown that serum hsCRP levels vary during the menstrual cycle in PMS women together with physical and mood manifestations, which advocates the contribution of low‐grade inflammation in the etiology of PMS (Puder et al, 2006 ). Several studies have reported that serum hsCRP, WBC, MPV and NLR are significantly associated with the presence of PMS and dysmenorrhea (Bahrami, Bahrami‐Taghanaki, et al, 2020 ; Bodur et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%